Defining Management Strategy for the Excellence Class Program during the 2019 Coronavirus Disease Pandemic - Rizki Syiam; Zainal Abidin; Khotibul Umam (The Faculty of Education and Teaching Training, 2022)
The purpose of this study is to describe and analyze the planning, implementation, and evaluation of the strategies for madrasa principals in the Coronavirus Disease 19 pandemic era in managing the superior class program at MTs Negeri 11 Banyuwangi. This research uses a qualitative approach which is research that produces descriptive data in the form of written or spoken words from people and observable behavior. The results of this study indicate that: focus 1. a). The school conducts a needs analysis. b). Schools set goals according to school targets. c). The school establishes several programs including teachers teaching subjects that are taught in accordance with qualifications and competence in their fields as well as schools preparing teacher training for online learners. focus 2. a). Availability of adequate electronics for teachers and students. b). The learning process through several applications and links to the learning process is given by the teacher. c). The teacher has followed the guidance of technology. focus 3. a). In the form of files via the Whatsapp application and instructions via video calls. b). Attendance system via Whatsapp and fill out Google form. c). Materials and evaluations are uploaded to Youtube and Google Sites. The head of the madrasa is the key that determines the success of the madrasa in achieving its goals. The head of the madrasa is required to always improve the effectiveness of the performance of the staff at the madrasa. The emergence of the Covid-19 Pandemic which has spread throughout the world including Indonesia has had an impact on all sectors. Not being left behind also has implications for the education sector, so it requires changes in systems and policies, even the way students learn is also required to follow established policies. Such as remote management, giving lots of assignments and a more flexible learning system, and so on. The head of the madrasa has a very decisive role in the progress of an educational institution. This is because the madrasa head has a very large role in developing an educational institution. For this reason, one of the ways that can be taken is through improving the quality of education management. The focus of the research is how to plan, implement and evaluate the strategy of the head of the madrasa in the era of the Coronavirus Disease 19 pandemic in managing the superior class program at MTs Negeri 11 Banyuwangi. The purpose of this study is to describe and analyze the planning, implementation, and evaluation of the strategies for madrasa principals in the Coronavirus Disease 19 pandemic era in managing the superior class program at MTs Negeri 11 Banyuwangi. This research uses a qualitative approach which is research that produces descriptive data in the form of written or spoken words from people and observable behavior. The results of this study indicate that: focus 1. a). The school conducts a needs analysis. b). Schools set goals according to school targets. c). The school establishes several programs including teachers teaching subjects that are taught in accordance with qualifications and competence in their fields as well as schools preparing teacher training for online learners. focus 2. a). Availability of adequate electronics for teachers and students. b). The learning process through several applications and links to the learning process is given by the teacher. c). The teacher has followed the guidance of technology. focus 3. a). In the form of files via the Whatsapp application and instructions via video calls. b). Attendance system via Whatsapp and fill out Google form. c). Materials and evaluations are uploaded to Youtube and Google sites